Shariah perspective on crypto as asset (Mal): justifying the needs of estate planning and inheritance of digital asset - Norazlina Abd Wahab,; Nur Syaedah Kamis,; Zairy Zainol,; Akhmad Affandi Mahfudz, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to analyze the crypto assets in the horizon of mal according to the shariah and further discuss the needs of estate planning and management of this digital asset. The invention of blockchain technology has enabled the existence of crypto asset. As crypto assets global users are forecasted to hit 1 billion users by the end of 2022, its adoption and demand are remarkable and continued to grow sustainably. Nevertheless, its status from shariah perspective whether the crypto assets are deemed to be permissible according to shariah are still debatable. In this study, a review of literature and interview with shariah experts were conducted to achieve the objective of this study. The study found that majority of scholars and shariah experts are in conformity that crypto assets can be considered as mal. The opinions justify the needs of estate planning and inheritance of digital asset such as crypto to be practised by the owners. This study further suggested some guidelines to ensure estate planning of crypto asset. The policymakers might find this study beneficial to various stakeholders including crypto owner, regulator, estate planner and digital asset exchange (DAX) in realizing estate planning and inheritance of crypto asset.